ERICA: patterns of alcohol consumption in Brazilian adolescents - Evandro Silva Freire Coutinho; Debora França-Santos; Erika da Silva Magliano; Katia Vergetti Bloch; Laura Augusta Barufaldi; Cristiane de Freitas Cunha; Maurício Teixeira Leite de Vasconcellos; Moyses Szklo (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the patterns of alcohol consumption in Brazilian adolescents. METHODS We investigated adolescents who participated in the Study of Cardiovascular Risks in Adolescents (ERICA). This is a cross-sectional, national and school-based study, which surveyed adolescents of 1,247 schools from 124 Brazilian municipalities. Participants answered a self-administered questionnaire with a section on alcoholic beverages consumption. Measures of relative frequency (prevalence), and their 95% confidence intervals, were estimated for the following variables: use of alcohol beverages in the last 30 days, frequency of use, number of glasses or doses consumed in the period, age of the first use of alcohol, and most consumed type of drink. Data were estimated for country and macro-region, sex, and age group. The module survey of the Stata program was used for data analysis of complex sample. RESULTS We evaluated 74,589 adolescents, who accounted for 72.9% of eligible students. About 1/5 of adolescents consumed alcohol at least once in the last 30 days and about 2/3 in one or two occasions during this period. Among the adolescents who consumed alcoholic beverages, 24.1% drank it for the first time before being 12 years old, and the most common type of alcoholic beverages consumed by them were drinks based on vodka, rum or tequila, and beer. CONCLUSIONS There is a high prevalence of alcohol consumption among adolescents, as well as their early onset of alcohol use. We also identified a possible change in the preferred type of alcoholic beverages compared with previous research.